Solve $$\cos(2 \sin ^{-1}(- x)) = 0$$

I get the answer $\frac{-1}{ \sqrt2}$

By solving like this

\begin{align}2\sin ^{-1} (-x )&= \cos ^{-1} 0\\ 2\sin^{-1}(- x) &= \frac\pi2\\ \sin^{-1}(- x) &= \frac\pi4\\ -x &= \sin\left(\frac\pi4\right)\end{align}

Thus $x =\frac{-1}{\sqrt2}$

But correct answer is $\pm\frac{1}{\sqrt2}$

Where am I going wrong?

  • 2
    $\begingroup$ You didn't take multiple values into account. Neither cos nor sin are one to to one. $\endgroup$ – fleablood Jun 8 '17 at 15:34

Okay so expand the double angle to get $\cos^2(\sin^{-1}(-x))-\sin^2(\sin^{-1}(-x)=0$.

This should give you $(1-(-x)^2)-(-x)^2=0$.

Finally you have $1-2x^2=0$.

Solutions are $\displaystyle \boxed{\pm \frac{1}{\sqrt{2}}}$.

  • $\begingroup$ Because cos^-1 only returns one value. You have to use symmetry to get the other value $\endgroup$ – Saketh Malyala Jun 8 '17 at 15:43
  • $\begingroup$ How did you get This should give you $(1-(-x)^2)-(-x)^2=0$. $\endgroup$ – Neha Gupta Jun 8 '17 at 15:49
  • $\begingroup$ remember $\cos(\sin^{-1}(x)) = \sqrt{1-x^2}$ by right angle trigonometry $\endgroup$ – Saketh Malyala Jun 8 '17 at 15:50
  • $\begingroup$ $\sin(\sin^{-1}(x))=x$ because sin is the inverse of $\sin^{-1}$ $\endgroup$ – Saketh Malyala Jun 8 '17 at 15:51

You need to solve $\cos \left(2 \arcsin(-x) \right) = 0$. Let $y = 2 \arcsin(-x)$ then $\cos y = 0$ so $y = \pi/2 \pm n\pi$. Then, $$ 2 \arcsin(-x) = \frac{pi}{2} \pm n\pi $$ which implies $$ x = -\sin \left( \frac{\pi}{4} \pm \frac{n\pi}{2} \right) $$

Can you simplify this?


Trig functions are not one-to-one. For example if $\sin x = \frac 12$ then $x$ might be equal to $\frac {\pi}6$, but $x$ could also be $\frac {5\pi}6$ or $\frac {13\pi}6$ or it could be any $2k\pi + \frac {\pi}6$ or $(2k+1)\pi - \frac {\pi} 6$.

So when we say $\sin^{-1} x = \theta$ we are not just saying that $\theta$ is the angle so that $\sin (\theta) = x$. There should be an infinite number of such angles. We are saying that $\theta$ is an angle so that $\sin (\theta) = x$ AND we are saying that $\frac {-\pi}2 \le \theta \le \frac {\pi}2$. For those two conditions there is only one possible theta.

So $\sin^{-1}(\sin x)$ may or MAY NOT be equal to $x$. For example $\sin^{-1}(\sin (\frac {5\pi}6)) = \sin^{-1}(\frac 12) = \frac {\pi}6 \ne \frac {5\pi}6$.

However $\sin^{-1}(\sin x) = x + 2k\pi$ for some integer $k$ or $\sin^{-1}(\sin x) = (2k+ 1)\pi - x$.

So 1) Because $\sin (x) = \sin (\pi - x)$ and $x = \frac {\pi}2 - (\frac {\pi}2 - x)$ and $\pi - x = \frac{\pi}2 + (\frac {\pi}2 - x)$ then $\sin^{-1}(x) = (\frac {\pi}2 \pm x) \pm 2k\pi)$.

$\frac {-\pi}2 \le sin^{-1}(x) \le \frac {\pi}2$

And 2) Because $\cos (x) = \cos(\pi+ x)$ we have $\cos^{-1}(\cos x) = x \pm k \pi$.

$0 \le \cos^{-1} (x) \le \pi$

So ....

$\cos (2\sin^{-1}(-x) ) = 0$

$-\frac {\pi}2 \le \sin^{-1}(-x) \le \frac {\pi}2$ so $-\pi \le 2\sin^{-1}(-x) \le \pi$ and $\sin^{-1}(-x) = \cos^{-1}(0) \pm k\pi = \frac {\pi}2 \pm k\pi$. So $2\sin^{-1}(-x) = \pm \frac {\pi}2$

And $\sin^{-1}(-x) = \pm \frac {\pi}4$

So $\sin (\pm \frac {\pi} 2) = -x$

So $\pm \frac {1}{\sqrt{2}} = -x$

So $x = \mp \frac {1}{\sqrt{2}}$


Let $\sin^{-1}(-x)=u\implies\sin u=-x$



Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.